Comparison between two pedicle screw augmentation instrumentations in adult degenerative scoliosis with osteoporosis - Xie, Yang (BioMed Central, 2011)
BACKGROUND: The operative treatment of adult degenerative scoliosis combined with osteoporosis increase following the epidemiological development. Studies have confirmed that screws in osteoporotic spines have significant lower-screw strength with more frequent screw movements within the vertebra than normal spines. Screws augmented with Polymethylmethacrylate (PMMA) or with autogenous bone can offer more powerful corrective force and significant advantages. METHODS: A retrospective analysis was conducted on 31 consecutive patients with degenerative lumbar scoliosis combined with osteoporosis who had surgery from December 2000. All had a minimum of 2-year follow-up. All patients had posterior approach surgery. 14 of them were fixed with pedicle screw by augmentation with Polymethylmethacrylate (PMMA) and the other 17 patients with autogenous bone. Age, sex and whether smoking were similar between the two groups. Surgical time, blood loss, blood transfusion, medical cost, post surgery ICU time, hospital day, length of oral pain medicines taken, Pre-and postoperative Oswestry disability index questionnaire and surgical revision were documented and compared. Preoperative, postoperative and final follow up Cobb angle, sagittal lumbar curve, correction rate, and Follow up Cobb loss were also compared. RESULTS: No significant differences were found between the autogenous bone group and Polymethylmethacrylate group with regards to all the targets above except for length of oral pain medicines taken and surgery cost. 2 patients were seen leakage during operation, but there is neither damage of nerve nor symptom after operation. No revision was needed. CONCLUSION: Both augmentation pedicle screw with Polymethylmethacrylate (PMMA) and autogenous bone treating degenerative lumbar scoliosis combined with osteoporosis can achieve a good surgical result. Less oral pain medicines taken are the potential benefits of Polymethylmethacrylate augmentation, but that is at the cost of more medical spending.